â€œLeave No One Behindâ€ in Education: Empowering Vulnerable Youth towards Self-Sustainability and Social Development - Suryani, Adi; Soedarso, Soedarso (International Journal of Community Service Learning, 2020)
Every human being has equal right to obtain proper education which prospectively promotes decent employment and life prosperity. Vulnerable children and youth are potential human resources who should be encouraged to develop themselves and meaningfully contribute to society. This study aims to explore education service and learning for encouraging orphanage youth at Panti Asuhan BJ Habibie-Surabaya to be self-sustained and potentially contributes to society. Qualitative method is adopted to meet research objectives. The data are collected through direct participant observation in a community service. The study indicates that life skill education promotes life values which support the orphans to face life challenges. Being able to be self-educated, developed and discover positive life meaning can be potential investment for the orphans to survive. The growth of contributing and meaningful vulnerable youth requires a caring society who provides just and encouraging climate for the vulnerable to learn, develop and promote intergenerational learning.